The Influence of the Air-coal Ratio on Transient Characteristics of the Ultra-supercritical Power Unit during the Load Cycling Processes - Yong ZHANG; Chaoqiang YIN; Yugang LIU; Bin ZHANG; Chunhong MO; Chaoyang WANG (Zhongguo dianli)
In order to study the influence of the air-coal ratio on the peak regulating characteristics of a coal-fired unit during load cycling transients, a dynamic model of a double-reheat ultra-supercritical coal-fired power plant with 660MW was established. The influence of the air-coal ratio on the live and reheat steam temperatures, the flowrates of the desuperheating water and the transient energy consumption was studied. A control scheme of air - coal ratio considering the steam temperature control effect and operational efficiency under different load cycling rates was proposed. The results show that, during the load cycling transient processes, a larger air-coal ratio benefits the stabilization of the live and reheat steam temperatures, while the average coal consumption rate of power during the transient process is higher. When the load cycling rate is equal to or less than 1%/min, a smaller air-coal ratio is preferred to reduce the average coal consumption by 1.2 g/(kW·h) during the load cycling transient process. When the load cycling rate is between 2%/min and 3%/min, a higher air-coal ratio is preferred to ensure that the deviations of the live and reheat steam temperatures can be controlled within 10℃．